Charter on the Protection of Historic Ruins – theory and practice. Examples from Lesser Poland - Janczykowski, Jan (Protection of Cultural Heritage, 2018)
The Charter on the Protection of Historic Ruins, adopted as the Resolution of the General Assembly of the Polish National Committee of ICOMOS on December 4th, 2012, has become a significant doctrinal document, supporting the conservation service in setting up recommendations for the owners of castle ruins and subsequently in the process of project documentation review. In Lesser Poland, there are several examples of ongoing works in this type of historic monuments. The present research examines the results of previous works in three castles: Tenczyn, Rabsztyn and Rożnów. Experience gained from these actions allows to review the utility of the Charter in practice.